Pengaruh Profitabilitas Terhadap Harga Saham Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021 - Swari Lintang Tenan (Jurnal Ilmiah Wahana Pendidikan, 2022)
The study aims to analyze the profitability of stock prices. The direct impact of profitability reflected by Return On Assets (ROA) and Return On Equity (ROE) on stock prices. The study population is consumer goods companies listed on the Indonesian Stock Exchange in 2019-2021. The results of this study show that ROA has a positive impact on stock prices, but it is not significant. ROE has only a small negative impact on the stock price. The results of this study are, in theory, expected to more fully reflect and explain the impact of return on equity and return on equity on stock prices. In addition, the book can be used practically as an input and reference material for consumer goods companies listed on the Indonesian Stock Exchange and as a portal of information on the impact of return on assets and return on equity on stock prices.